Strategic sophistication and trading profits: An experiment with professional traders - Marco Angrisani; Marco Cipriani; Antonio Guarino (Federal Reserve Bank of New York, 2022)
We run an experiment where professional traders, endowed with private information, trade an asset over multiple periods. After the trading game, we gather information about the professional traders' characteristics by having them carry out a series of tasks. We study which of these characteristics predict profits in the trading game. We find that strategic sophistication, as measured in the Guessing Game (for example, through level-k theory), is the only significant determinant of professional traders' profits. In contrast, profits are not driven by individual characteristics such as cognitive abilities or behavioral traits. Moreover, higher profits are due to the ability to trade at favorable prices rather than to the ability to earn higher dividends. Comparing these results to those of a sample of students, we show that whereas cognitive skills are important for students, they are not for traders, whereas the opposite is the case for strategic sophistication.
Keywords: C93; G11; G14; 330; experiments; financial markets; professional traders; strategic sophistication